Cell Performance Determining Parameters in High Pressure Water Electrolysis. (1st September 2016) - Suermann, Michel; Schmidt, Thomas J.; Büchi, Felix N.
Abstract: When hydrogen is used for energy applications, then often elevated pressure is required, i.e. up to 1000 bar for hydrogen refueling stations. When polymer electrolyte electrolyzers are operated at elevated pressures, to reduce external mechanical compression needs, the thermodynamically expected cell voltage increase with pressure is not generally observed. Consequently, beneficial processes have to compensate for the increased work performed. In this paper, the influence of the operating pressure up to 100 bar on the cell voltage behavior is investigated in detail. Data from galvanotstatic polarization curves up to 4 A/cm 2 combined with high frequency resistance measurements are analyzed using a zero-dimensional Tafel model. It shows that beneficial processes with increasing pressure are related to both the kinetic and mass transport overpotentials. At current densities above 1 A/cm 2 about two thirds of the overpotential gain can be related to reaction kinetics. Based on the Tafel model approach an increase of the apparent exchange current density by a factor of 4 to 7 is observed for the pressure increase from 10 to 100 bar. In contrast, the Tafel slope is independent of pressure and only the expected increase with temperature (73 to 81 mV/dec) for 30 to 70 °C is observed. Mass transport losses decrease with pressure. At 50 °C and 2 A/cm 2, increasing the pressure from 1 to 100 bar results in a decrease of the mass transport overpotential from 130 to 80 mV.